Strategi Pemasaran Kangkung Tanpa Pestisida (Studi Kasus di Kelompok Tani Putra Tani Desa Kemang Kecamatan Kemang Kabupaten Bogor) - Dyah Budibruri Wibaningwati; Anak Agung Eka Suwarnata; Syavira Kurnia Afifah (AGRIFITIA : Journal of Agribusiness Plantation, 2022)
One of the locations for harvesting water spinach in West Java is from the Putra Tani Farmers Group in Kemang Village, Bogor Regency, which was established in 2009. The Putra Tani Farmers Group produces water spinach and markets it in Bogor Regency and Bogor City. Marketing of water spinach by farmer groups is considered not optimal, so it is necessary to formulate an appropriate marketing strategy by analysing internal factors (strengths and weaknesses) and external factors (opportunities and threats) of water spinach marketing. This type of research is a qualitative descriptive study with 25 respondents who are members of the Putra Tani Farmers' Group using non-probability sampling. The analytical method adopts SWOT. From this, several alternative marketing strategies for water spinach were obtained, namely maintaining the quality of water spinach first so that the price is higher than water spinach, which is applied with chemical fertilizers and pesticides. Second, participating in exhibitions or establishing independent markets to expand product promotion. The third is to improve the packaging quality and reduce water spinach damage, thereby increasing the price. Fourth, expanding sales to various restaurants. Fifth, increase product promotion through the market (online market) to meet consumer needs for a healthy lifestyle. Keywords: strategy; marketing; water spinach; SWOT